1977
DOI: 10.1002/art.1780200114
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroid inhibition of nonphagocytic discharge of lysosomal enzymes from human neutrophils

Abstract: Glucocorticosteroids and mineralocorticosteroids were tested for their capacity to inhibit the nonphagocytic discharge of two lysosomal enzymes-a cartilage matrixdegrading neutral protease and ,8-glucuronidase-from highly purified human neutrophils. Lysosomal enzyme discharge from neutrophils adherent to nonphagocytizable, immobilized, heat-aggregated IgC was inhibited by the four glucocorticosteroids-methylprednisolone sodium succinate, triamcinolone acetonide hemisuccinate, paramethasone acetate, and hydroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…However, as in this study, the killing capacity in physiological cortisol treated PMN was not different from control, it can be concluded that although phagocytosis may be enhanced with physiological concentrations of cortisol, the ultimate capability of the PMN to reduce bacterial numbers is not affected. This is in agreement with Smith (1977) and Ignarro (1977), who demonstrated that physiological concentrations of glucocorticoids had no effect on PMN Iysossomal enzyme release in vitro. As viability lost was not observed, the decrease of activity observed on the cortisol incubated cells can not be attributed to an increase of dead cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, as in this study, the killing capacity in physiological cortisol treated PMN was not different from control, it can be concluded that although phagocytosis may be enhanced with physiological concentrations of cortisol, the ultimate capability of the PMN to reduce bacterial numbers is not affected. This is in agreement with Smith (1977) and Ignarro (1977), who demonstrated that physiological concentrations of glucocorticoids had no effect on PMN Iysossomal enzyme release in vitro. As viability lost was not observed, the decrease of activity observed on the cortisol incubated cells can not be attributed to an increase of dead cells.…”
Section: Discussionsupporting
confidence: 92%
“…Because microscopic observations indicated that neutrophils degranulated during contact with pseudohyphae, the effects of hydrocortisone were then studied. Besides the well-known association between corticosteroid therapy and invasive candidiasis (4,5), cortisone may inhibit release of lysosomal enzymes from neutrophils (46). Hydrocortisone inhibited damage to Candida pseudohyphae by neutrophils at levels (10-1 ,uM) which may be reached in vivo after pharmacologic doses.…”
Section: Discussionmentioning
confidence: 96%
“…This con cept has been challenged by studies demonstrating that neutrophil lyso somes (the original studies were performed on liver lysosomes) are not stablized even by very high concentrations of corticosteroids (105). Other studies on lysosomes have demonstrated that high concentrations of in vitro corticosteroids can inhibit the release of lysosomal enzymes from neutro phils (99,106,107). Again, the relevance of this to the in vivo situation must be raised.…”
Section: Neutrophilmentioning
confidence: 92%